Market philosophy and information privacy - Park, Yong Jin (Javnost (Ljubljana), 2011)
This article examines U.S. policy shaping of personal information flow in its historical trajectory. The analysis newly draws on the notion of the marketplace ideal in privacy debate and analyses a regulatory continuum that an online information protection regime is the product of active formulation of a policy principle. Proxy regulation that attributes the function of privacy protection to discrete commercial domains is analysed in analogy with the diversity principle of broadcasting. Alternative Internet policy models are discussed beyond the oversimplified dichotomy between market and government. In a critique of the Federal Trade Commission's latest proposal of"Do Not Track List," a thesis is advanced to encourage a simplified user interface with a forceful measure that can intervene in the marketplace.
Keywords: United States of America; ZDA; trg; svoboda informiranja; svoboda govora; informacije; elektronski mediji; svetovni splet; privacy; zasebnost; pravica do zasebnosti